Surgical Implications of Innervation Pattern of the Triceps Muscle: A Cadaveric Study - Chaware, Prashant Nashiket; Santoshi, John Ashutosh; Patel, Manmohan; Ahmad, Mohtashim; Rathinam, Bertha A. D. (Journal of Hand and Microsurgery, 2018)
The innervation pattern of triceps is complex and not fully comprehended. Anomalous innervations of triceps have been described by various authors. We have attempted to delineate the nerve supply of the triceps and documented the anomalous innervations of its different heads. The brachial plexus and its major branches (in the region of the axilla and arm) and triceps were dissected in 36 embalmed cadaver upper limbs. Long head received one branch from radial nerve in 31 (86%) specimens. Four (11%) specimens received two branches including one that had dual innervation from the radial and axillary nerves, and one (3%) specimen had exclusive innervation from a branch of the axillary nerve. Medial head received two branches arising from the radial nerve in 34 (94%) specimens. One (3%) specimen received three branches from the radial nerve whereas one (3%) had dual supply from the radial and ulnar nerves. Lateral head received multiple branches exclusively from the radial nerve, ranging from 2 to 5, in all (100%) specimens. Knowledge of the variations in innervation of the triceps would not only help the surgeon to avoid inadvertent injury to any of the nerve branches but also offers new options for nerve and free functional muscle transfers.
Keywords: triceps; innervation pattern; nerve transfer; nerve injury; brachial plexus branches; surgical approach